2020
DOI: 10.1101/2020.08.31.276253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxycodone self-administration activates the mitogen-activated protein kinase/mitogen- and stress-activated protein kinase (MAPK-MSK) signaling pathway in the rat dorsal striatum

Abstract: To identify signaling pathways activated by oxycodone self-administration (SA), Sprague-Dawley rats self-administered oxycodone for 20 days using short-access (ShA, 3 h) and long-access (LgA, 9 h) paradigms. Animals were euthanized two hours after SA cessation and dorsal striata were used in post-mortem molecular analyses. LgA rats escalated their oxycodone intake and separated into lower (LgA-L) or higher (LgA-H) oxycodone takers. LgA-H rats showed increased striatal protein phosphorylation of ERK1/2 and MSK1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 90 publications
3
9
0
Order By: Relevance
“…This elevation in responding persisted on WD30 [Figure 2C; WD1 vs. WD30: F (1,28) = 40.40, Tukey's post hoc p = 0.012]. These findings are consistent with prior studies of the incubation of craving for oxycodone (e.g., previous works 12,14,30 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This elevation in responding persisted on WD30 [Figure 2C; WD1 vs. WD30: F (1,28) = 40.40, Tukey's post hoc p = 0.012]. These findings are consistent with prior studies of the incubation of craving for oxycodone (e.g., previous works 12,14,30 ).…”
Section: Resultssupporting
confidence: 88%
“…Recent studies have reported incubation of oxycodone craving. 12,14,30,31 The goals of the first experiment were to verify that incubation of craving occurs under our experimental conditions and to assess the duration of changes in drug-seeking. NAc tissue from these rats was then used to examine whether this incubation was accompanied by changes in AMPAR subunit surface expression (see next section).…”
Section: Oxycodone Craving Incubates Over the First 15 Days Of Withdr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this known biological function, the MAP kinase pathway was the most enriched GO molecular function term associated with the set of differentially expressed genes in opioid cases versus controls (P adj < 0.01) (Figure 1I) (Chen et al, 2013;Kuleshov et al, 2016) . Both the input transcription factors to the 388 loci (FOS AP1 factors) and output MAPK genes are consistent with known addiction pathways (Al-Hasani and Bruchas, 2011) (Blackwood et al, 2021) (Browne et al, 2020) (Qiao et al, 2021) (Brynildsen et al, 2020).…”
Section: Identification Of Homogeneous H3k27ac Hypoacetylation Eventssupporting
confidence: 61%
“…< 1×10 -7 ) (Figure 1B,C, Table S2). An exemplar locus linked to target gene DUAL-SPECIFICITY PHOSPHATASE 4 (DUSP4) in DLPFC promoter capture Hi-C data, involved in the addiction-relevant GPCR and MAPK signaling pathways (Blackwood et al, 2021;Qiao et al, 2021), is shown in Figure 1D. Strikingly, no significant hyperacetylated peaks in cases were found.…”
Section: Identification Of Homogeneous H3k27ac Hypoacetylation Eventsmentioning
confidence: 98%